The Role of Teachers in Human Resource Development Through Increasing Digital Literacy - Panggabean, Erika Christine; br Manullang, Endang Juliati; Naibaho, Frainskoy Rio (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service activity is an effort aimed at increasing understanding and digital literacy skills among the community, especially through the important role of teachers in this process. Digital literacy is an important key in the current digital era, where the ability to use information and communication technology effectively is very necessary. Through the role of teachers as agents of change, it is hoped that society, in this case students, can increase their knowledge and skills in digital literacy, so that they are able to face challenges and take advantage of opportunities offered by technological developments. The methods used in this activity are lectures and discussions, where the presentation of the material is carried out in 2 sessions. From the results of the activities that have been carried out, it can be concluded that teachers are not only able to improve soft skills but also hard skills by studying and mastering supporting applications in learning.